Radium Isotopes Levels in Drinking-Water Samples - S.A. Amin; A.A. Jassim (Engineering and Technology Journal, 2017)
Water is one of the most necessary substances on earth. In order to survive, all plants, animals and humans must drink water, and there is no life on earth if there is no water. Hence, water should be uncontaminated with any type of carcinogenic materials such as heavy metals, radioactivity or other pollutants and must be clear. In this work, drinking-water samples were examined and analyzed for radionuclide levels using NaI gamma spectrometer, as well as, estimated annual effective dose (AED) has been calculated. The values of 226Ra, 228Ra and 40K levels range from (0.12-0.35)Bq.L-1, (0.09-0.16)Bq.L-1 and (31.66-49.25)Bq.L-1, with mean values 0.29, 0.12 and 43.39 Bq.L-1, respectively. The total estimated annual effective dose gained from the combined ingestion of radium isotopes is found to start from 0.07 mSv.y-1 to 0.14 mSv.y-1 with an average value of 0.12 mSv.y-1. Therefore, the total (AED) for all samples is below the world standard value of 1mSv.y-1. Hence, drinking water is considered safe from the radiological point view and does not cause any significant health hazard for Baghdadi inhabitants.